2020
DOI: 10.1016/j.jhazmat.2019.121230
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis and source apportionment of metals in riverine sediments of a rural-urban watershed

Abstract: Quantitative assessment of metal sources in sediments is essential for implementation of source control and remediation strategies. This study investigated metal contamination in sediments to assess potential ecological risks and quantify pollutant sources of metals (Cu, Zn, Pb, Cd, Cr, Co and Ni) in the Wen-Rui Tang River watershed. Total and fraction analysis indicated high pollution levels of metals. Zinc and Cd posed high ecological risk based on the risk assessment code, with the highest ecological risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 49 publications
3
26
1
Order By: Relevance
“…Likewise, the spatial Moran's I index is also sensitive to outliers, although the I index is strongly suggestive of polluted sources. Xia et al (2020) and Dash et al (2020) found that disproportional events commonly influence the outlier values in sediment source studies, such as when an urban area is enclosed by commercial and residential sites. Thus, the PMF is highly sensitive to outlier values (Supplemental Data, Figure S5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, the spatial Moran's I index is also sensitive to outliers, although the I index is strongly suggestive of polluted sources. Xia et al (2020) and Dash et al (2020) found that disproportional events commonly influence the outlier values in sediment source studies, such as when an urban area is enclosed by commercial and residential sites. Thus, the PMF is highly sensitive to outlier values (Supplemental Data, Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…Appraisal of metal contamination status, co‐occurrence networks, source apportionment, and ecotoxicological risk evaluation (which are important environmental determinants) is essential for constructing efficient water security regulation and management strategies on a national basin scale. Several studies have appraised the pollution status and ecotoxicological risks of metals in riverine sediments in different parts of the world, for instance, Ustaoğlua and Islam (2020) in Giresun, Northeast Turkey, and Ji et al (2019) in Baiyangdian Lake, China (also see Bhuiyan et al 2017; Xu et al 2019; Khan et al 2020; Xia et al 2020). To determine different metal concentrations, numerous indices have been constructed, such as the geo‐accumulation index (Igeo), enrichment factor, risk index, and toxicity unit in riverine sediments (Siddiqui and Pandey 2019; Niu et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that Cr was significantly positively correlated with Pb (r = 0.951, p < 0.01) and Th (r = 0.803, p < 0.05). It suggests that the three metals (Cr, Pb, and Th) may have the same sources or sedimentary characteristics [39]. Concentrations of U are highly correlated with Th, which indicates that both of these metals might have originated from the uranium mining activities.…”
Section: Source Identification Of Metals In Sedimentsmentioning
confidence: 94%
“…Studies have shown that atmospheric deposition, vehicular transportation-related activities and metallic building envelopes resulting from agricultural, domestic and industrial activities are among the major pollution sources of urban watersheds [7] [8]. The partitioning of sources is further complicated by source interactions [9].…”
Section: Introductionmentioning
confidence: 99%